WIARA A INNE TYPY POZNANIA - SIEŃKOWSK, Marcin (Civitas et Lex, 2014)
The characteristics of the knowledge of God through the religion faith is consequence of subject – that one’s overtopped the epistemic powers of human – which is accessible merely in that way. The aim of Belief is supernatural and it consists in union with God through getting to know his nature. The method of the religious faith is an engagement of the intellect and a will the recognised subject. The religious faith is a different cognition toward other types of knowledge. It is also the cognition which assumes a former natural acquired knowledge. A leap of faith in that what was deemed for truth needs activities of intellect.